A Jiggy McCue Story : Do Bugs Have Bottoms? - Michael Lawrence; Glenn Murphy (Orchard Books, 2011)
Glenn Murphy's very funny question and answer book will solve some of life's great unknowns. Then flip over and let Jiggy McCue show you what really happened at the dawn of mankind in this fantastically funny caveman caper.
Keywords: Narrative Nonfiction -- Narrative Nonfiction